Aided- and self-assembly of liquid crystalline nanoparticles in bulk and in solution: computer simulation studies. Issue 1 (2nd January 2023) - Slyusarchuk, A.; Yaremchuk, D.; Lintuvuori, J.; Wilson, M. R.; Grenzer, M.; Sokołowski, S.; Ilnytskyi, J.
ABSTRACT: We review computer simulation studies of aided and self-assembly of nanoparticles that are decorated with liquid crystalline (mesogenic) ligands, termed hereafter as liquid crystalline nanoparticles (LCNPs). In bulk, LCNPs self-assemble into ordered morphologies, typically displaying a polydomain structure. We demonstrate that a range of monodomain morphologies can be grown by changing the density of ligands and employing external fields of specific symmetry, which act on mesogens. It is also demonstrated that the speed of self-assembly of LCNPs with chromophoric (e.g. azobenzene) mesogens can be increased by applying illumination at a certain wavelength and polarisation. Another case study covers the formation of an interconnected macromolecular network in a solution of the LCNPs in a polar solvent. Here, the network structure depends strongly on the decoration pattern of the LCNPs. Finally, the adsorption of LCNPs on a compatible liquid crystalline brush is discussed with a focus on the prerequisites and optimal conditions for this phenomenon. The review demonstrates the ability of classical particle-based models to produce a molecular-based understanding of the structure and interactions of LCNPs, and also to reproduce a wide set of physicochemical phenomena related to LCNP aided- and self-assembly processes. Graphical abstract: uf0001